School participation of children with disability: The case of San Remigio and Mandaue City, Cebu, Philippines - Adrian D. Agbon; Christian D. Mina (Philippine Institute for Development Studies (PIDS), 2017)
In the Philippines, women and children with disabilities were found to have lower literacy and school participation rates, and generally have lower educational attainment, than male persons with disability (PWDs) and nondisabled children. This paper is part of the joint project of the Philippine Institute for Development Studies and the Institute of Developing Economies. It looked into the school participation of children with disability in Mandaue City and San Remigio, Cebu, Philippines. Using survey data (collected involving PWD enumerators) and key informant interviews with various stakeholders, the study found that school participation among PWD children is generally low in both study sites. Possible reasons for low school participation are: type and severity of impairment, distance of school (especially in rural area, San Remigio), household size, and income. Some recommendations include making sure that assistive devices given to PWD children match their needs, possible learning livelihood and basic health care modules/trainings for parents, exploring ways to train more teachers (including the Alternative Learning System or ALS) to handle children with disabilities, and possible local government unit partnerships to provide venues for the ALS. Lastly, the study recommends pushing for more awareness to make schools not just "child friendly" but also "PWD friendly".
Keywords: 330; school participation; Person with disability (PWD) children; San Remigio; Mandaue City; Cebu; City; Philippines